Magnitude and Antimicrobial Susceptibility Profile of Salmonella Recovered from Export Abattoirs Located in East Shewa, Ethiopia - Alemu A; Regassa F; Kebede N; Ambachew R; Girma M; Asefa Z; Tsegaye W (Infection and Drug Resistance, 2022)
Abayneh Alemu,1,2 Fikru Regassa,2 Nigatu Kebede,3 Rozina Ambachew,1 Musse Girma,3 Zerihun Asefa,4 Wondewosen Tsegaye1 1Department of Medical Microbiology and Parasitology, St. Paul’s Hospital Millennium Medical College, Addis Ababa, Ethiopia; 2Department of Livestock Resource Sector, Ministry of Agriculture, Addis Ababa, Ethiopia; 3Department of Animal Health and Research Unit, Akililu Lemma Institute of Pathobiology, Addis Ababa University, Addis Ababa, Ethiopia; 4Department of Clinical Studies, College of Veterinary Medicine and Agriculture, Addis Ababa University, Bishoftu, Oromia State, EthiopiaCorrespondence: Abayneh Alemu, Addis Ababa, Ethiopia, Tel +251913169301, Email abayalemu12@gmail.comBackground: Salmonella is one of the most common foodborne pathogens globally, and it remains a major public health concern with the increasing concern of the emergence and spread of antimicrobial-resistant strains. In Ethiopia, the information on the prevalence of Salmonella is scarce in export abattoirs.Objective: To estimate the magnitude and antimicrobial susceptibility profile of Salmonella recovered from export abattoirs located in East Shewa, Ethiopia.Methods: A cross-sectional study was conducted from January to October 2020. In the study, 345 samples were collected from five export abattoirs using a systematic random sampling method. There were 150 carcass swabs (100 from goats and 50 from sheep), 60 goat skin swabs, 60 knife swabs, and 75 human stools. The isolates were identified and characterized using standard bacteriological procedures and confirmed using Salmonella genus-specific primer by polymerase chain reaction. Isolates were subjected to antimicrobial susceptibility to 14 antibiotics using the Kirby–Bauer disk diffusion method, and the results were assessed by using Clinical and Laboratory Standards Institute 2018.Results: Of the 345 samples, 21 (6.08%; 95% CI 4.9– 11.2%) were positive for Salmonella. The specific prevalence of Salmonella in carcass, skin, and knife swabs were 10 (6.67%; 95% CI 3.5– 11.19%), 7 (11.67%; 95% CI 5.70– 23.00%), and 4 (6.67%; 95% CI 2.50– 16.64%), respectively. There was no statistically significant difference in the occurrence of Salmonella among export abattoirs and types of samples (P> 0.05). In the current study, Salmonella was not isolated from sheep carcass and human stool samples. Among the 21 Salmonella isolates, 7 (33.3%) were resistant to at least 1 of the 14 antimicrobial agents tested and 2 (9.04%) of isolates were resistant to two antibiotics, tetracycline, and streptomycin. All isolates were susceptible to kanamycin, chloramphenicol, cephalothin, gentamycin, and ceftriaxone.Conclusion: Salmonella was detected in carcass, skin, and knife samples from export abattoirs, which can have serious public health consequences. Some commonly used drugs in veterinary medicine have developed antimicrobial resistance. Therefore, sufficient sanitation at abattoirs, appropriate cooking of carcasses, and rational drug use is strongly advised. Further in-depth study such as serotyping and antimicrobial-resistant gene identification is recommended.Keywords: antimicrobial susceptibility, carcass, export abattoirs, prevalence, Salmonella